QAnon, authoritarianism, and conspiracy within American alternative spiritual spaces - Conner, Christopher T. (Frontiers in Sociology, 2023)
QAnon, in the United States, has become something of household name due to its role in the January 6th insurrection, and because of the relatively high degree of media attention it has received. While such coverage has been useful in understanding this conspiracy movement, it has also painted a picture of QAnon that is incomplete. This paper examines three separate cultural entry points not typically associated with the movement—Yoga and Wellness Groups, Neo-Shamanistic circles, and Psychics. By colonizing these spaces QAnon was able to embed itself, disguise its abrasive features, and go largely unnoticed by the general public. This study reminds us of studies of authoritarianism from the 1950s which found that it can take root in a variety of spaces, and that within each of us lie potentially fascistic tendencies—even those seeking enlightenment, through alternative practices (Adorno et al 1950).